Idebenone Alleviates Neuroinflammation and Modulates Microglial Polarization in LPS-Stimulated BV2 Cells and MPTP-Induced Parkinson’s Disease Mice - Yan, Aijuan; Liu, Zhihua; Song, Lu; Wang, Xijin; Zhang, Yu; Wu, Na; Lin, Jingya; Liu, Ying; Liu, Zhenguo (Frontiers in Cellular Neuroscience, 2019)
Background: Idebenone is an antioxidant and a coenzyme Q10 analog that has been used to treat neurodegeneration disease. Some studies show idebenone exerts anti-inflammatory effects. However, whether idebenone can be used to reduce the neuroinflammation in Parkinson’s disease (PD) has been little studied. Methods: The study investigated the potential anti-inflammatory effects of idebenone in vitro and in vivo, using cell models of Lipopolysaccharide (LPS)-simulated BV2 cells and animal models of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD with or without idebenone. To verify how idebenone exerts its effects on the BV2 cell activation and PD model, we performed the mechanistic studies in vitro and in vivo. Results: In vitro study showed that pretreatment with idebenone could attenuate the production of pro-inflammatory factors in LPS-stimulated BV2 cells and promoted a phenotypic switch from the M1 state to the M2 state. Mechanistically, idebenone reduced the activation of the MAPK and NF-κB signaling pathway upon LPS stimulation. Furthermore, in vivo experiments confirmed that pretreatment with idebenone could ameliorate MPTP-induced neurodegeneration and modulate microglia phenotypes through inhibition of the MAPK and NF-κB signaling pathway in the SN. Conclusion: These results suggest that idebenone ameliorates the neurological deficits related to PD and this effect is partly mediated by inhibiting the neuroinflammation and modulating microglia phenotypes.